Etiology and clinical significance of peripheral blood cytokines in geriatric patients with pulmonary infections - Xue, Ming; Song, Qiuming; Feng, Kaijun (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to characterize the etiological patterns and assess the clinical relevance of serum inflammatory cytokine levels in elderly patients with pulmonary infections.MethodsA retrospective cohort study was conducted involving 75 geriatric inpatients with radiologically confirmed pulmonary infections and 75 age-matched non-infected controls at He Fei Third Clinical College of Anhui Medical University from January 2022 to December 2024. Serum cytokines (IL-2, IL-5, IL-6, IL-8, IFN-γ, TNF-α) were measured using chemiluminescence immunoassay. Baseline characteristics and cytokine profiles were compared, and logistic regression with ROC analysis was performed. Key severity anchors (ICU vs. general ward, ventilator requirement, and baseline room-air SpO₂) were abstracted at admission.ResultsCompared to age-matched non-infected controls, infected patients had a higher prevalence of diabetes (p = 0.012) and smoking (p = 0.003), longer length of hospital stay (p < 0.001), higher levels of IL-6, IFN-γ, and TNF-α, and lower levels of IL-2 (all p < 0.05). In the infected group, a total of 88 pathogen isolates were identified, with a predominance of Gram-negative bacteria (64.8%). Elevated levels of IL-6 (OR = 3.17) and TNF-α (OR = 2.89) were identified as independent predictors of infection, while higher levels of IL-2 were found to be protective (OR = 0.42). TNF-α (AUC = 0.934) and IL-6 (AUC = 0.904) showed strong diagnostic performance.ConclusionThe cytokine profile showing increased levels of IL-6 and TNF-α alongside decreased levels of IL-2 is significantly associated with pulmonary infections in the elderly, supporting its potential use as a biomarker set for early diagnosis and risk stratification.